PENGEMBANGAN DINDING POLYSTYRENE DENGAN PERKUATAN KAWAT LOKET - OKVIANTI IRLAN, ADE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One type of plastic which is non degradable is called polystyrene (PS) or usually it is mentioned by styrofoam. This kind of PS plastic is generally used as an electronic wrapper or foil, styrofoam food place, one time used only drinking galss, and many other usages. The important problem faced by the industrial of polystyrene (PS) is the disposal or waste of this plastic as it is categorized as a non degradable disposal. Based on this fact, the researcher studied the use of polystyrene (PS) as a lightweight aggregate in a mixed concrete material. polystyrene, the concrete resulted is in the form of light weight one which can be functionalized as a room partition. In this research the researcher tried to utilize the disposal of polystyrene by making use of it as a wall panel formed by a lightweight concrete. The polystyrene wall panel is strengthened by locket filament given a press for as much as 2 MPa varied by the cement of 250 kg/m3, 300 kg/m3, 100% polystyrene and fas 0.4. The research resulted that the average polystyrene kubic pressure and volume for the containing cement of 250 kg/m3 and 300 kg/m3 was 6,735 MPa, 5,906 MPa, and 1308 kg/m3, 1350 kg/m3. The test of water absorbtion of polystyrene cube for containing cement of 250 kg/m3 and 300 kg/m3 was 13,62% and 14,36%. The test of average elastical modulus for containing cement of 250 kg/m3 and 300 kg/m3 resulted for 372,99 MPa and 441,57 MPa. Further, the test of refraction of cement containing cement of 250 kg/m3 and 300 kg/m3 for the maximum force mean of polystyrene wall panel was 6,39 kN and 6,90 kN. Average deflection at the maximum force was 6,67 mm and 3,51 mm, and so far the allowed deflection was as much as 4,33 mm. compressive strength, stifness and flexible moment capacity on the average of the polystyrene wall panel containing cement of for 250 kg/m3 and 300 kg/m3 was 1,67 MPa, 1,81 MPa, 1395,35 N/mm, 2751,88 N/mm and 88135,105 Nmm, 87694,631 Nmm. The test of wall panel pressure on polystyrene wall containing the concrete of 250 kg/m3 and 300 kg/m3 was 112,63 kN and 127,70 kN. To continue, the pressure power achieved was 6,05 MPa and 6,95 MPa. The pressure of 2MPa resulted on better power pressure than that of lower power pressure. Key words : wall of polystyrene, locket filium, pressure of 2 MPa.